Competition and cooperation between high-speed rail and air transportation services in Europe - Albalate, Daniel; Bel, Germà; Fageda, Xavier (Journal of transport geography, 2015)
•Airlines subject to HSR competition reduce the number of seats offered in the route.•Frequencies might not be reduced as much by airlines, to keep competing with HSR.•Results vary across countries depending on HSR network design and length.•HSR stations in hub airports can feed air demand, thus partially compensating effects from competition. New high-speed rail (HSR) lines may have an enormous influence on the provision of air services. The attention has been devoted to competition between both transportation modes but in some cases HSR services may also have an intermodal complementary role with air transportation. By taking a supply oriented empirical analysis, we study the impact of HSR on air service frequencies and seats offered by airlines in large European countries. We emphasize the distinction between routes with and without a hub airport as an endpoint and we also examine the influence of the location of the HSR station. We generally find direct competition between HSR and airlines, but we also provide some evidence that HSR can provide feeding services to long haul air services in hub airports, particularly in hub airports with HRS stations.